2003
DOI: 10.1021/es020839+
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Specific Congener Profile of 40 Polybrominated Diphenyl Ethers in River and Coastal Sediments from Portugal

Abstract: Forty polybrominated diphenyl ethers (PBDEs), from mono- through hepta-brominated, were analyzed in river and coastal sediment samples of the eight main river basins of Portugal to investigate the occurrence, geographical distribution, and detailed congener profiles. Thirty-two sediment samples taken along the different rivers from inland to the open sea revealed an increase toward the river mouth with a total PBDE concentration of 20 ng/g-dw, and levels decreased to 0.5 ng/g-dw in coastal sediments. PBDEs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 32 publications
9
32
0
Order By: Relevance
“…Dividing the PBDEs according to their bromination grade, tetra-brominated congeners were the most representative of the fingerprint, contributing on average 66%, followed by penta-BDEs (23%) and hexa-and hepta-BDEs (4%). This trend was similar to that obtained in other sediment samples from European (de la Cal et al 2003;Lacorte et al 2003), North American (Hale et al 2003), and Asian (Binelli et al 2007;Chen et al 2009) aquatic environments.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Dividing the PBDEs according to their bromination grade, tetra-brominated congeners were the most representative of the fingerprint, contributing on average 66%, followed by penta-BDEs (23%) and hexa-and hepta-BDEs (4%). This trend was similar to that obtained in other sediment samples from European (de la Cal et al 2003;Lacorte et al 2003), North American (Hale et al 2003), and Asian (Binelli et al 2007;Chen et al 2009) aquatic environments.…”
Section: Resultssupporting
confidence: 90%
“…The current PBDE pollution of the lagoon sediments can be considered low to moderate. PBDE lagoon pollution was similar to that revealed in Asian coastal environments, as Minh et al (2007) in Tokyo Bay, Japan (with a range of 0.051 to 3.6 ng g −1 d.w.), and in China by Yang et al (2003) in the Quingdao near-shore (with a range of 0.1 to 5.5 ng g −1 d.w.), while it was higher than that revealed in the Yangtze River Delta (with a range of n.d. to 0.55 ng g −1 d.w.; Chen et al 2006).In regard to the European situation, Lacorte et al (2003) revealed that Portuguese river sediments are generally more polluted than coastal ones, and the latter presented concentrations perfectly comparable to those measured in the present study. In addition, a monitoring study of de la Cal et al (2003) identified similar levels (in the range of 0.86 to 2.49 ng g −1 d.w.) of seven BDE congeners (BDE-47, BDE-99, BDE-100, in some river and marine sediments collected around Barcelona and Tarragona (Spain).…”
Section: Comparison With Other Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…With a structure that is similar to other environmentally persistent contaminants (i.e., polychlorinated dioxins, polychlorinated furans, and polychlorinated biphenyls), an intrinsic chemical stability, high recalcitrance to different types of degradation and high toxicity to living organisms (de Wit 2002;McDonald 2002), PBDEs have been recognized as an environmental contaminant of foremost concern. Because of their ubiquitous use and their lipophilic and inert characteristics, soil and sediment are very likely a sink for PBDEs (Lacorte et al 2003;Hassanin et al 2004). Microorganisms, existing in intimate contact with the soil, are very sensitive to low concentrations of contaminants and exhibit rapid responses to soil perturbation (Schloter et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies reported total concentrations of 17 different polybrominated diphenyl ether congeners in sediments at 4 different sites located along the international river section (1 site located in the adjacent coastal area) ranging from 0.3 to 4.8 ng g -1 (Lacorte et al 2003). Recent data also showed low heavy metal concentrations (Cd, Cr, Cu, Ni, Pb and Zn) measured in the sediments and Corbicula fluminea (Müller, 1774) tissues at 6 different sites (Sites 1, 4, 9, 11, 12 and 13; Fig.…”
Section: Abiotic Characterizationmentioning
confidence: 99%